FUNCTIONAL FOODS IN MANAGING DIABETES - R.SUJA PANDIAN (International Journal of Pharma and Bio Sciences, 2013)
Diabetes, emerging as a pandemic, is a major health problem predisposing to micro and macrovascular complications. Traditional Indian diets are functional because they are enriched with antioxidants, dietary fiber and probiotics.The present paper reviews on the scientific information of common Indian foods with anti-diabetic activity, which is used as functional foods and ingredients in the traditional medical system. It is indeed the time to give more attention to these functional food ingredients as target medicinal foods in order to prevent or slow down the development of diabetes.